Media Influence on Political Development: Framing Analysis of Aceh's Poverty Reduction Programs - Ali, Chaidir; Purnomo, Eko Priyo; Husein, Rachmawati (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
This article explores the role of mass media in shaping public perceptions of poverty alleviation programs in Aceh. Framing analysis based on Robert N. Entman’s theory, this research aims to understand how the mass media chooses focus, point of view and emphasis to present information about the issue of poverty and programs to overcome it. This article describes the complexity of Aceh’s history, especially the armed conflict which had a significant impact on political and economic life. The research is motivated by the need to understand how mass media plays a key role in shaping public opinion regarding poverty alleviation efforts in Aceh. The research method uses a qualitative approach with framing analysis as the main analytical tool. This research uses Ncapture and NVivo to collect and analyze data in the form of news and journal articles related to poverty alleviation programs in Aceh. The sample used was news related to the poverty alleviation program in Aceh published by the mass media detik.com, then analyzed using framing techniques to identify the framing patterns used by the mass media in reporting the poverty alleviation program in Aceh. The results of this analysis show that Aceh still faces serious challenges in overcoming poverty, and the mass media plays an important role in shaping public perceptions of this issue. This article contributes to an understanding of the political dynamics and construction of news related to poverty in Aceh and provides a basis for improving communication strategies in poverty alleviation efforts.Keywords: Media role, development politic, framing, poverty reduction program, AcehABSTRAKArtikel ini mengeksplorasi peran media massa dalam membentuk persepsi masyarakat terhadap program pengentasan kemiskinan di Aceh. Analisis framing berdasarkan teori Robert N. Entman, penelitian ini bertujuan untuk memahami bagaimana media massa memilih fokus, sudut pandang, dan penekanan untuk menyajikan informasi tentang isu kemiskinan dan program-program penanggulangannya. Artikel ini menggambarkan kompleksitas sejarah Aceh, terutama konflik bersenjata yang berdampak signifikan pada kehidupan politik dan ekonomi. Penelitian dilatarbelakangi kebutuhan untuk memahami bagaimana media massa memainkan peran kunci dalam membentuk opini publik terhadap upaya pengentasan kemiskinan di Aceh. Metode penelitian menggunakan pendekatan kualitatif dengan analisis framing sebagai alat analisis utama. Penelitian ini memanfaatkan Ncapture dan NVivo untuk mengumpulkan dan menganalisis data berupa berita dan artikel jurnal terkait program pengentasan kemiskinan di Aceh. Sampel yang digunakan adalah berita-berita terkait program penanggulangan kemiskinan di Aceh yang dipublikasikan oleh media massa detik.com, kemudian dianalisis menggunakan teknik framing untuk mengidentifikasi pola framing yang digunakan media massa dalam melaporkan program penanggulangan kemiskinan di Aceh. Hasil analisis menunjukkan bahwa Aceh masih menghadapi tantangan serius dalam mengatasi kemiskinan, dan media massa memainkan peran penting dalam membentuk persepsi publik terhadap isu tersebut. Artikel ini memberikan kontribusi dalam pemahaman tentang dinamika politik dan konstruksi berita terkait kemiskinan di Aceh serta memberikan landasan bagi perbaikan strategi komunikasi dalam upaya pengentasan kemiskinan.Kata Kunci: Peran media, politik pembangunan, framing, program penanggulangan kemiskinan, Aceh